Impact of comorbidity in elderly prostate cancer patients treated with brachytherapy - Chiumento, Costanza; Fiorentino, Alba; Cozzolino, Mariella; Caivano, Rocchina; Clemente, Stefania; Pedicini, Piernicola; Fusco, Vincenzo (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To analyze the correlations among comorbidity and overall survival (OS), biochemical progression-free survival (b-PFS) and toxicity in elderly patients with localized prostate cancer treated with 125I brachytherapy. Methods: Elderly men, aged ≥65 years, with low-intermediate risk prostate cancer, were treated with permanent 125I brachytherapy as monotherapy. Comorbidity data were obtained from medical reports using age-adjusted Charlson comorbidity index (a-CCI). The patients were categorized into two age groups (3). Toxicity was scored with Radiation Therapy Oncology Group (RTOG) scale. Results: From June 2003 to October 2009, a total of 92 elderly patients underwent prostate brachytherapy, including 57 men (62%) with low-risk prostate cancer, and 35 men (38%) with intermediate-risk prostate cancer. The median age of patients was 75 years (range, 65-87 years). Forty-seven patients (51%) had a-CCI ≤3 and 45 patients (49%) a-CCI >3. With a median follow-up period of 56 months (range, 24-103 months), the 5-year actuarial OS and b-PFS were 91.3% and 92.4% respectively, without statistical significance between two Charlson score groups. Toxicity was mild. None of the patients experienced gastrointestinal (GI) toxicity, and only 4 patiens (4%) experienced late genitourinary (GU) grade-3 (G3) toxicity. No correlation between acute GU and GI toxicity and comorbidity was showed (P=0.50 and P=0.70, respectively). Conclusions: Our data suggest that elderly men with low-intermediate risk prostate cancer and comorbidity can be considered for a radical treatment as 125I low-dose rate brachytherapy.